Pengaruh Kandungan Protein Ransum yang Berbeda terhadap Kecernaan dan Fermentabilitas Rumen Sapi Perah secara In vitro: The Effect of Different Feed Protein Content on Digestibility and Fermentability of Dairy Rumen using In vitro (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
The most of protein requirement for cows is fulfilled by microbial protein. Increasing the protein from ration usually influences the milk production in dairy cows. However, the availability of dietary protein should support rumen ecosystem through microbial activity in the fermentation and digestion process. The aim of this study was to evaluate the protein levels of dairy cow ration on the rumen fermentability and digestibility using an in vitro method. Randomized block design with three levels of protein ration as a treatment and three times taken of rumen liquor as a block. The treatments were: R1= ration with low protein; R2= ration with moderate protein and R3= ration with high protein. The measured parameters were rumen fermentability (total VFA, N-NH3 and pH), in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility  (IVOMD). The results showed that there were significantly increase in dry and organic matter digestibility (p